1999
DOI: 10.1097/00004647-199909000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cytokine Release from Peripheral Blood Cells after Acute Stroke

Abstract: Cytokines interleukin (IL)-6 and tumor necrosis factor (TNF)-alpha can play pathogenetic or protective roles in stroke. They are increased in the brain after experimental ischemia and in the CSF of patients with stroke. However, their presence in the periphery is still controversial. To determine the source and time-course of cytokines in blood of stroke patients, IL-6 and TNF-alpha release from blood cells and serum levels were determined in 40 patients on days 1 through 2, 4, 10, 30, and 90 after stroke. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
131
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(146 citation statements)
references
References 40 publications
12
131
1
2
Order By: Relevance
“…33 TNF-a release from blood cells and serum levels of TNF-a were found to be elevated during the acute phase following stroke compared with healthy controls. [34][35][36] Furthermore, increased levels of TNF-a in the cerebral spinal fluid and serum of acute stroke patients has been associated with increased severity of postischemic neuropathology 37 and polymorphism of the TNF gene have been associated with susceptibility to ischemic stroke. 32 IL-6 is a pleiotropic cytokine involved in inflammatory processes and like IL-1 is able to induce acute inflammatory responses such as fibrinogen and C-reactive protein production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 TNF-a release from blood cells and serum levels of TNF-a were found to be elevated during the acute phase following stroke compared with healthy controls. [34][35][36] Furthermore, increased levels of TNF-a in the cerebral spinal fluid and serum of acute stroke patients has been associated with increased severity of postischemic neuropathology 37 and polymorphism of the TNF gene have been associated with susceptibility to ischemic stroke. 32 IL-6 is a pleiotropic cytokine involved in inflammatory processes and like IL-1 is able to induce acute inflammatory responses such as fibrinogen and C-reactive protein production.…”
Section: Resultsmentioning
confidence: 99%
“…The C-reactive protein, an important peripheral inflammatory marker, is strongly associated with risk for stroke. [38][39][40] Although a clear picture of the role of IL-6 in stroke has not yet been elucidated, an increase in IL-6 production following cerebral ischemia has been described in several clinical studies 21,34,41,42 and elevated levels of the IL-6 cytokine have been correlated with severity and clinical outcome of stroke. 28,43,44 Furthermore, polymorphisms of the promoter IL-6 gene have been associated with stroke 45,46 and the IL-6 system has been associated with acute inflammatory response after stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of the molecules participating in this pathogenic cascade causing neuronal damage probably represents a chance to recognize possible serum markers of ischemic stroke useful to a diagnostic algorithm of acute ischemic stroke. Increases of the proinflammatory cytokines interleukin-1␤, IL-6 and TNF-␣ have been detected in the ischemic cortex 1 h after middle cerebral artery (MCA) occlusion in experimental models of brain ischemia [8], and several studies have reported elevations of these proinflammatory cytokines in peripheral blood as well as in cerebrospinal fluid in patients with ischemic stroke [15][16][17][18][19][20]. Nevertheless, pathogenesis of brain ischemia involves both immuno-inflammatory and thrombotic mechanisms, so a good diagnostic panel for ischemic stroke should include a representative biomarker of both these pathogenic aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel with IL-1a Higher level in CSF IL-6 (231 ± 313 pg/ml) Ferrarese et al (1999) 40 (20) 1-90 days…”
Section: Serum Interleukin-6 In Stroke Patientsmentioning
confidence: 99%